1988
DOI: 10.1111/j.1528-1157.1988.tb05789.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Therapy in Resistant Epilepsy

Abstract: It is now established that the overall prognosis for epilepsy is good and that remission will occur in at least 75% of patients following adequate treatment with monotherapy. Patients who fail to respond to monotherapy, who are not suitable for surgery, and who continue to have frequent seizures may have to be considered for an alternative drug regimen. A review of the literature indicates that complete seizure control with adjunctive treatment is rare, but improved seizure control can be obtained in up to 40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
(13 reference statements)
1
10
0
1
Order By: Relevance
“…The steady-state concentrations achieved in patients in this study are of the same order as those found in epileptic patients receiving therapeutic doses of clobazam (Callaghan & Goggin, 1984). In our patients receiving chronic dosing, steady-state concentrations were much higher in males than in females.…”
Section: -Juuuisupporting
confidence: 79%
“…The steady-state concentrations achieved in patients in this study are of the same order as those found in epileptic patients receiving therapeutic doses of clobazam (Callaghan & Goggin, 1984). In our patients receiving chronic dosing, steady-state concentrations were much higher in males than in females.…”
Section: -Juuuisupporting
confidence: 79%
“…하는 효소이다 (Dulac and Arthuis, 1984;Elwes et al, 1984;Callaghan and Goggin, 1988 (Stohs, 1995;Douglas, 1998 (Cohen and Doherty, 1987;Behl et al, 1994;Bejma and Ji, 1999). …”
Section: Hydroxyl Radical Scavenging 효과 측정mentioning
confidence: 99%
“…Clobazam (CLB) is a 1,5-benzodiazepine commonly used as adjunct therapy in the treatment of resistant epilepsy (Callaghan & Goggin, 1988;Robertson, 1986). It is metabolized to Ndesmethylclobazam, which has also been successfully used in the treatment of refractory epilepsy .…”
Section: Introduction Methodsmentioning
confidence: 99%